Retroviral integrations contribute to elevated host cancer rates during germline invasion - Gayle K. McEwen (Nature Portfolio, 2021)
Koalas are susceptible to neoplasms, which are related to infection with the Koala retrovirus. Here, the authors use DNA sequencing to show that the retroviral insertion sites cluster near known cancer genes and demonstrate a high mutational load associated with the germline invasion of the virus.